Evolution's cauldron: Duplication, deletion, and rearrangement in the mouse and human genomes - Kent, W. James (National Academy of Sciences, 2003)
This study examines genomic duplications, deletions, and rearrangements that have happened at scales ranging from a single base to complete chromosomes by comparing the mouse and human genomes. From whole-genome sequence alignments, 344 large (>100-kb) blocks of conserved synteny are evident, but these are further fragmented by smaller-scale evolutionary events. Excluding transposon insertions, on average in each megabase of genomic alignment we observe two inversions, 17 duplications (five tandem or nearly tandem), seven transpositions, and 200 deletions of 100 bases or more. This includes 160 inversions and 75 duplications or transpositions of length >100 kb. The frequencies of these smaller events are not substantially higher in finished portions in the assembly. Many of the smaller transpositions are processed pseudogenes; we define a “syntenic” subset of the alignments that excludes these and other small-scale transpositions. These alignments provide evidence that ≈2% of the genes in the human/mouse common ancestor have been deleted or partially deleted in the mouse. There also appears to be slightly less nontransposon-induced genome duplication in the mouse than in the human lineage. Although some of the events we detect are possibly due to misassemblies or missing data in the current genome sequence or to the limitations of our methods, most are likely to represent genuine evolutionary events. To make these observations, we developed new alignment techniques that can handle large gaps in a robust fashion and discriminate between orthologous and paralogous alignments.